2008
DOI: 10.1108/09534810810915736
|View full text |Cite
|
Sign up to set email alerts
|

Narratives as sensemaking accounts: the case of an R&D laboratory

Abstract: Purpose -While conventional wisdom suggests that sensemaking is targeted towards consensual understanding of the organization's intent and action, the objective of this study is to explore a different angle of sensemaking, namely, a situation of change and crisis in which the sensemaking process focuses on presenting the organization's members with an alternative understanding of its worldview, norms, and values. Design/methodology/approach -The paper is based on a three-year ethnographic field study. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…A schism between older, senior scientists and younger, junior scientists and technicians has also been observed by Landau and Drori (2008). In their study of R&D professionals, they noted that a number of employees were critical of ''old guard scientists'' who they described as ''.…”
Section: Changing Identities: From Scientists To Managersmentioning
confidence: 91%
See 2 more Smart Citations
“…A schism between older, senior scientists and younger, junior scientists and technicians has also been observed by Landau and Drori (2008). In their study of R&D professionals, they noted that a number of employees were critical of ''old guard scientists'' who they described as ''.…”
Section: Changing Identities: From Scientists To Managersmentioning
confidence: 91%
“…Although scientists at Oil Co appeared to have become somewhat resigned to the erosion of their professional power, some scientists in other R&D contexts have managed to maintain a considerable amount of control over their. For instance, in their study of R&D professionals in the Defense Sector in Israel, Landau and Drori (2008) observed that: ''Creativity and freedom were strongly emphasized, with the general atmosphere allowing scientists to do as they pleased, with an almost total absence of deadlines'' (p. 707). These contrasting positions perhaps reflect a difference in sector (i.e.…”
Section: Shifting Time Orientations and Professional Emphasismentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a great deal of work that has engaged qualitative methods in studying managers' narratives and/or which has adopted a narrative analytical approach to understanding management and organizations, there is relatively little that has used data acquired through extended written narratives of managers (Down and Reveley, 2009;Fronda and Moriceau, 2008;Landau and Drori, 2008;Letiche et al, 2008;Vickers, 2008;Watson, 2009). Indeed, in a literature search for this paper the author found no references for any study that had collected written narratives from practicing managers.…”
Section: Methodology: Collecting and Analyzing Narrativesmentioning
confidence: 99%
“…46 process studies, 1 process/variance combination study and 3 variance studies) varies with respect to their samples. A broad range of organizations are represented including education institutions (Brown & Humphreys, 2003;Gioia et al, 1994;Gioia & Chittipeddi, 1991;Gioia & Thomas, 1996;Kezar, 2013), financial institutions (Chreim, 2006;Heracleous & Barrett, 2001;Isabella, 1990), consulting firms (Greenberg, 1995), government departments (Weber & Manning, 2001) and committees (Abolafia, 2010), healthcare organizations (Bartunek et al, 2006;Dutton et al, 2001;Riesenmy, 2010), insurance companies (Hope, 2010), a private defense laboratory (Landau & Drori, 2008), an engineering firm (Teulier & Rouleau, 2013), a clothing manufacturer (Rouleau, 2005), retailers (Sonenshein, 2009, 2010010) and even a toy manufacturer (Luscher & Lewis, 2008). The extant research on sensemaking about change has explored this phenomenon in both public and private sector organizations, including a number of organizations from the healthcare sector.…”
Section: Samples Utilizedmentioning
confidence: 99%